Translation of Education-Related Terminology From Czech Language to English - GREGAR Jan CZ (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2018)
The article introduces the readers to selected terminological findings acquired in recent years while translating monographs and articles dealing with educational science. The purpose of this article is also to react on the trends, which are manifesting themselves in an intensive communication of Czech scientific and educational workers in the English language and also the demand put on students who have to submit their abstracts and key words together with their theses. In this connection, we deal with more or less frequent terms of educational science, didactics and other related fields. Keywords : educational science, pedagogy, didactics, methodology, terminology, translation, Czech language, English language